Pyoderma Gangrenosum following Pacemaker Implantation: A Case Report and Review of Literature - Noura Ayoubi; Zaydi Javeed; Raymond Cutro; Brooke T. Baldwin (Case Reports in Cardiology)
Pyoderma gangrenosum (PG) is a rare neutrophilic dermatosis characterized by noninfectious, inflammatory, ulcerating lesions. Pathergy can be seen in these patients, whereby minor trauma or surgery can result in the development of PG ulcerations. Here, we present a case of PG following pacemaker implantation. A 76-year-old male with a history of rheumatoid arthritis presented to the cardiology team with symptomatic bradycardia. Indications for implantation were met, and the procedure was performed in a routine fashion. The patient returned to clinic for follow-up four days later, complaining of pain at the incision site, coupled with erythema and purulent drainage. Consultations with an infectious disease specialist and a dermatologist were requested, and the diagnosis of pyoderma gangrenosum was considered. The patient underwent device removal and received systemic corticosteroids at a dose of 1 mg/kg prednisone with complete lesion healing in 3 weeks. While being maintained on steroids, the patient underwent reimplantation of a new pacemaker on the contralateral side without complication and had a normal postoperative course. We present this case report, along with the review of literature, in order to highlight the multidisciplinary approach to management, which requires dermatologic treatment in order to achieve pacemaker success.